1991
DOI: 10.1177/030098589102800202
|View full text |Cite
|
Sign up to set email alerts
|

Neospora-like Protozoal Infections Associated with Bovine Abortions

Abstract: Abstract. Eighty bovine fetuses with presumed protozoal infections from a previous 2-year retrospective study were examined by immunohistochemistry using antisera against Neospora caninum. In 66 (83%) of the fetuses, protozoa were found that reacted positively with anti-N. caninum sera. In three (4%) additional fetuses, protozoa identified as Sarcocystis species did not react, and in two fetuses (3%) single protozoal clusters were found only in hematoxylin and eosin-stained slides. A group of 20 fetuses were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
82
0
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 16 publications
3
82
0
5
Order By: Relevance
“…1,13 Case reports from several geographic regions in the USA have confirmed that the disease is more widespread in dairy cattle, but it also occurs in beef animals. 3,6,8,10,11,14 Transplacental transmission is currently the only known route of infection, but a vertebrate definitive host is suspected. 5 The fetal lesions of bovine neosporosis have been described in previous reports.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,13 Case reports from several geographic regions in the USA have confirmed that the disease is more widespread in dairy cattle, but it also occurs in beef animals. 3,6,8,10,11,14 Transplacental transmission is currently the only known route of infection, but a vertebrate definitive host is suspected. 5 The fetal lesions of bovine neosporosis have been described in previous reports.…”
mentioning
confidence: 99%
“…5 The fetal lesions of bovine neosporosis have been described in previous reports. [2][3][4]6,8,[10][11][12]14 It is believed there is a preliminary placentitis from which the organism is distributed through the blood to fetal tissues. In field cases of neosporal abortion, the organism has been identified in brain, spinal cord, striated muscle, liver, kidney, lung, adrenal gland, and adipose tissue, and it is associated with either granulomatous or nonsuppurative inflammation.…”
mentioning
confidence: 99%
“…Neosporosis has emerged as an important disease in bovines worldwide and is related to reproductive loss in these animals, causing abortions and neonatal mortality (ANDERSON et al, 1991;BARR et al, 1991;THORNTON;THOMPSON;DUBEY, 1991;WOUDA et al, 1999). Establishing the diagnosis of neosporosis is therefore important, as a step in re-breeding and possibly switching dams according to their history of abortions (DUBEY; SCHARES; ORTEGA-MORA, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Neospora caninum (N. caninum) is a recently identified apicomlexan parasite and a major cause of abortion in dairy cattle worldwide [1,8]. At present, immunohistochemistry and the indirect fluorescent antibody test (IFAT) are mainly used for diagnosing neosporosis [8,29].…”
mentioning
confidence: 99%